DINAMIKA TENAGA KERJA SEKTOR PERTANIAN DI PROVINSI SULAWESI UTARA - Esry Laoh (Sam Ratulangi University, 2012)
This study aims to determine the dynamics of agricultural labor force of North Sulawesi Province. Re-search location in Manado (July to August 2010). Collecting data is secondary data research. The data were processed using the calculation of share of labor and labor force growth rate calculations. The re-sults showed employment growth rate of agriculture sector decreased by 5.78 percent per annum in the period of 2000-2009. While employment in non-agricultural sector increased by 1.78 percent each year. This indicates there is the tendency of structural transformation of agriculture labor to non-agricultural sector. Low tendency of Trade will be able to influence farmers to reduce or stop activities that agribusi-ness will affect the size of the agricultural labor share. Labor share of agriculture sector on the basis of education level is dominated by the level of primary education during the period 2007-2009 but its labor force growth rate has decreased each year in both rural and urban areas. Labor share of the agricultur-al sector based on the age group was dominated by the age of 55 years and above over the 2007-2009 period and is indicated by increasing the growth rate of labor force in rural and urban areas especially in urban areas despite a decline each year that tend to occur due to an increased energy agricultural labor in rural areas. Labor share of agriculture sector by district / city dominated by Bolaang Mongon-dow during the period 2007-2009, although rates of employment growth in agriculture sector has de-creased each year in both rural and urban areas. Labor share of agriculture sector based on the out-pouring of work hours was dominated by workers who work full (>35 hours) during the period 2007-2009 despite the decline in employment growth rates in both rural and urban areas each year.Keywords: Dynamics of Agricultural Labor Force, Structural Transformation, Labor Share